PENGARUH PENGUKURAN KINERJA DENGAN ECONOMIC VALUE ADDED DAN EARNINGS PER SHARE TERHADAP RETURN SAHAM PADA PERUSAHAAN YANG TERGABUNG DALAM INDEKS LQ45 DI BURSA EFEK INDONESIA - Roghiebah Jadwa Faradisi; Muhammad Nuryatno Amin (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2012)
Company’s financial performance can be measured using Economic Value Added and Earnings Per Share. The existence of these two methods, will demonstrate the company’s ability to earn a profit for a certain period and whether the company will create value or not. The purpose of this study is to prove the effect of the company’s financial performance using EVA and EPS on stock returns. Research study is a test of the hypothesis, the causal relationship. The sampling technique using purposive sampling, a total of 34 companies in 2010-2012.The analytical method used is regression testing. The results obtained from this study are incorporated in EVA LQ45 companies showed a positive effect on stock returns over the period 2010-2012.This indicates that the management company has succeeded in creating shareholder value and improve the life of the owner of the company, because the return is given as expected. However, this study also proved that the EPS has no effect on the stock return.